Oral health status, dental anxiety, and behavior‐management problems in children with oppositional defiant disorder. (26th December 2015) - Aminabadi, Naser A.; Najafpour, Ebrahim; Erfanparast, Leila; Jamali, Zahra; Pournaghi‐Azar, Fatemeh; Tamjid‐Shabestari, Shabnam; Shirazi, Sajjad
Abstract : Mental disorders have been shown to affect children's oral health. This study was carried out to investigate the oral health status, dental anxiety (DA), and behavior‐management problems (BMPs) during dental treatment in 6‐ to 9‐yr‐old children with oppositional defiant disorder (ODD)/attention‐deficit hyperactivity disorder (ADHD). The study and control groups included 40 children with ODD/ADHD and 80 normal children, respectively. All participants received an amalgam restoration. During the procedure, the children's behavior was assessed using the Frankl Rating Scale and the Verbal Skill Scale. Parents rated their children's DA using the parental version of the Children's Fear Survey Schedule‐Dental subscale (CFSS‐DS). Comorbid anxiety disorders were assessed using the Kiddie‐Sads‐Present and Lifetime Version questionnaire. Oral health status was assessed using the gingival index and the decayed, missing, and filled teeth score for permanent (DMFT) and primary (dmft) teeth. The findings showed that DA and BMPs were significantly higher in children with ODD/ADHD than in the controls. Furthermore, the frequency of DA and BMPs was higher in children with both ODD/ADHD and a comorbid anxiety disorder than in those without comorbid anxiety disorder. Children with ODD/ADHD had significantly higher DMFT/dmft scores than those in the control group, whereas the difference in gingival index was not statistically significant. In conclusion, children with ODD/ADHD had higher levels of DA, BMP and poorer oral health status.